Electroencephalography as a tool to predict cerebral oxygen metabolism during deep-hypothermic circulatory arrest in neonates with critical congenital heart diseaseCentral MessagePerspective - Gerard H. Laurent, ScB; Tiffany S. Ko, PhD; Kobina G. Mensah-Brown, MD, MS; Constantine D. Mavroudis, MD, MSC, MTR; Marin Jacobwitz, CRNP, PhD; Nicolina Ranieri, BSc; Susan C. Nicolson, MD; J. William Gaynor, MD; Wesley B. Baker, PhD; Daniel J. Licht, MD; Shavonne L. Massey, MD, MSCE; Jennifer M. Lynch, MD, PhD (JTCVS Open, 2023)
Objectives: Recent research suggests that increased cerebral oxygen use during surgical intervention for neonates with congenital heart disease may play a role in the development of postoperative white matter injury. The objective of this study is to determine whether increased cerebral electrical activity correlates with greater decrease of cerebral oxygen saturation during deep hypothermic circulatory arrest. Methods: Neonates with critical congenital heart disease requiring surgical intervention during the first week of life were studied. All subjects had continuous neuromonitoring with electroencephalography and an optical probe (to quantify cerebral oxygen saturation) during cardiac surgical repair that involved the use of cardiopulmonary bypass and deep hypothermic circulatory arrest. A simple linear regression was used to investigate the association between electroencephalography metrics before the deep hypothermic circulatory arrest period and the change in cerebral oxygen saturation during the deep hypothermic circulatory arrest period. Results: Sixteen neonates had both neuromonitoring modalities attached during surgical repair. Cerebral oxygen saturation data from 5 subjects were excluded due to poor data quality, yielding a total sample of 11 neonates. A simple linear regression model found that the presence of electroencephalography activity at the end of cooling is positively associated with the decrease in cerebral oxygen saturation that occurs during deep hypothermic circulatory arrest (P < .05). Conclusions: Electroencephalography characteristics within 5 minutes before the initiation of deep hypothermic circulatory arrest may be useful in predicting the decrease in cerebral oxygen saturation that occurs during deep hypothermic circulatory arrest. Electroencephalography may be an important tool for guiding cooling and the initiation of circulatory arrest to potentially decrease the prevalence of new white matter injury in neonates with critical congenital heart disease.